Physical demands of international pre-matches and their relationship with the official match statistics among adolescent basketball players - Gál-Pottyondy Anna; Mészáros Áron; Farkasinszki Gábor; Molnár László; Kiss Rita M.; Trzaskoma Lukasz (Biomedical Human Kinetics, 2025)
The study aimed to investigate the effects of age and gender on game-related performance (GRP) and the associations between GRP data and official game-related statistics (GRS).